Pengaruh Akar Tuba (Derris elliptica) Terhadap Mortalitas Dan Intensitas Serangan Keong Mas (Pomacea canaliculata L.) Pada Padi - Widya Ningrum; Lutfi Afifah; Sugiarto Sugiarto; Anton Yustiano (AGRICA, 2023)
Rice (Oryza sativa L.) is a rice-producing plant that is one of the staple foods for the world's population, especially Indonesia. One of the factors causing a decrease in rice production is pests, the main pest of rice plants is the golden snail. The golden snail pest attack occurs on rice plant seedlings, namely in the vegetative phase. The purpose of this study was to determine the effect of giving plant-based pesticides tuba root extract (Derris elliptica) on the mortality and pest intensity of the golden snail (Pomacea canaliculata L.) on rice plants (Oryza sativa L.) Inpari 32 variety. The method used was experimental (trial) using a single factor Randomized Block Design (RBD) with 6 treatments with 5 replications so there were 30 experimental units. Treatment of D. elliptica tuba root extract concentration on rice (Oryza sativa L.) treatment A (Control), B (5g/L), C (7g/L), D (9g/L), E ( 11g/L), and F (13g/L). Tuba root extract at a concentration of 13g/L is the best concentration which gives the highest mortality of 81.60% with the lowest attack intensity value of 29.84%. The LC50 value of the tuba root extract on the golden snail was 2.64g/L, the minimum value was 0.37g/L and the maximum was 4.164 g/L. LT50 takes a minimum of 1 day and a maximum of 9 days with an average time of 6-5 days. The results of calculating the correlation between mortality and the intensity of golden snail attacks on tall rice plants are -0.60. Administration of tuba root extract of D. eliptica was effective against the mortality of the golden snail P. canaliculata and the intensity of the attack by the golden snail P. canaliculata on rice (Oryza sativa L.).